الكفايات اللازمة للطلبة المعلمين أثناء إعدادهم لمهنة التدريس بجامعة البحر الاحمر - عيسى بلال موسى, بلال (جامعة الوادي University of Eloued, 2018)
تهدف الدراسة إلى معرفة الكفايات اللازمة للطلبة المعلمين أثناء اعدادهم لمهنة التدريس بجامعة البحر الاحمر . استخدم الباحثان المنهج الوصفي التحليلي . وتكونت عينة الدراسة 65 معلماً ومعلمة . واستخدم الباحث الإستبانة للمعلمين وتكونت من فقرة . كشفت نتائج الدراسة أن تقديرات المعلمين المتعاونين على الكفايات اللازمة للطالب/المعلم جاءت في مستوى التقدير العالي ، بينما أظهرت النتائج أن الكفايات الشخصية احتلت المرتبة الاولى من بين الكفايات التي يمارسها أثناء التدريب الميداني . كما أظهرت النتائج أن الطلبة المعلمين يواجهون عدداً من المشكلات المتعلقة بمرحلتي التطبيق والتقويم . وأوصى الباحث بضرورة تخصيص فترة كافية للتربية العملية ، لإكساب الطالب/المعلم المهارات اللازمة لمزاولة مهنة التدريس بشكل فاعل. ABSTRACT: The aim of the study is to know the competencies required for the students of the teachers during their preparation for the teaching profession at the University of the Red Sea. The researchers used the descriptive analytical approach. The study sample consisted of 65 teachers and teachers. The researcher used the questionnaire for teachers and consisted of a paragraph. The results of the study revealed that the estimates of the cooperating teachers on the competencies needed for the student/ teacher came at the high level of appreciation, while the results showed that personal competencies ranked first among the competencies exercised during field training. The results also showed that the teacher students face a number of problems related to the application and evaluation stages. The researcher recommended the need to allocate sufficient time to practical education, to give the student/ teacher skills necessary to practice the teaching profession effectively.
مقال
Keywords: الكفايات - الاعداد - الطالب المعلم; Competencies; Students Teachers; preparation; Teaching profession; University of the Red Sea